Bike Desks in the Office: Physical Health, Cognitive Function, Work Engagement, and Work Performance. Issue 12 (December 2016) - Torbeyns, Tine; de Geus, Bas; Bailey, Stephen; De Pauw, Kevin; Decroix, Lieselot; Van Cutsem, Jeroen; Meeusen, Romain
Abstract : Objective: The aim of this study was to examine the longitudinal effect of implementing bike desks in an office setting on physical health, cognition, and work parameters. Methods: Physical health, cognitive function, work engagement, and work performance measured before (T0) and after (T2) the intervention period were compared between office workers who used the bike desk (IG, n  = 22) and those who did not (CG, n  = 16). Results: The IG cycled approximately 98 minutes/week. The IG showed a significantly lower fat percentage and a trend toward a higher work engagement at T2 relative to T0, while this was not different for the CG. No effects on other parameters of health, cognition, or work performance were found. Conclusions: Providing bike desks in the office positively influences employees' fat percentage and could positively influence work engagement without compromising work performance.